2022
DOI: 10.1007/s00590-022-03379-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of surgical site infections after cervical spine surgery: results of a single-center cohort study adhering to multimodal preventive wound control protocol

Abstract: Purpose The incidence of surgical site infections is considered a relevant indicator of perioperative and postoperative care quality. The aim of this study is to analyze and evaluate SSIs after elective cervical spine surgery under the guidance of our preventive multimodal wound protocol. Methods A monocentric observational cohort study analyzed 797 patients who underwent cervical spine surgery from 2005 to 2010 (mean age 51.58 ± 11.74 year, male 56.09%, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The occurrence of SSIs in neurosurgical procedures, including cervical spine surgeries, is influenced by multiple factors such as the nature of the surgical procedure, patient-specific characteristics, and the implementation of preventive strategies. A noteworthy study that analyzed a cohort of 797 patients undergoing cervical spine surgery reported an even lower incidence of SSIs (0.25%) [28]. In their retrospective analysis, Cao et al scrutinized a significant sample of 808 cases involving patients who underwent clean neurosurgical operations.…”
Section: Antibiotic Prophylaxis In Various Specialtiesmentioning
confidence: 99%
“…The occurrence of SSIs in neurosurgical procedures, including cervical spine surgeries, is influenced by multiple factors such as the nature of the surgical procedure, patient-specific characteristics, and the implementation of preventive strategies. A noteworthy study that analyzed a cohort of 797 patients undergoing cervical spine surgery reported an even lower incidence of SSIs (0.25%) [28]. In their retrospective analysis, Cao et al scrutinized a significant sample of 808 cases involving patients who underwent clean neurosurgical operations.…”
Section: Antibiotic Prophylaxis In Various Specialtiesmentioning
confidence: 99%
“…Compared with lumbar surgeries, cervical surgery cases were associated with a significantly lower rate of infection 5 . Meanwhile, posterior cervical spine surgeries cases had a significantly higher rate of infection than anterior cervical surgeries cases with consequences ranging from superficial to deep infection 6,7 . Cervical laminoplasty is the most widely used procedure in posterior cervical surgery 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“… 5 Meanwhile, posterior cervical spine surgeries cases had a significantly higher rate of infection than anterior cervical surgeries cases with consequences ranging from superficial to deep infection. 6 , 7 Cervical laminoplasty is the most widely used procedure in posterior cervical surgery. 8 , 9 Because it prevents the formation of epidural scarring while maintaining the integrity of the posterior neck muscles.…”
Section: Introductionmentioning
confidence: 99%